Ukuran Perusahaan Memoderasi Pengaruh Kepemilikan Asing Dan Komisaris Independen Terhadap Kebijakan Dividen di Indonesia - Ni Putu Adinda Putri Gayatri; Lucy Sri Musmini; I Made Pradana Adiputra (Owner : Riset dan Jurnal Akuntansi, 2025)
This study was conducted with the aim of testing and analyzing how foreign ownership and independent commissioners affect dividend policy with company size as a moderating variable. This study uses panel data analysis with a quantitative approach. The population of this study includes companies listed in the Kompas 100 Index on the Indonesia Stock Exchange that publish financial reports and distribute dividends during 2021-2023, the sample was obtained through purposive sampling technique and a total of 42 companies were obtained as samples, which were then analyzed using STATA software. This study uses multiple linear regression analysis and the Moderated Regression Analysis (MRA) test. The results of the study show that foreign ownership and independent commissioners have a significant positive effect on dividend policy. Meanwhile, company size has not been able to moderate the influence of foreign ownership and independent commissioners on dividend policy. This study presents novelty by showing that in the context of large companies in Indonesia, especially the Kompas 100 Index, company size does not strengthen the influence of foreign ownership or independent commissioners on dividend policy. This highlights that the complexity of governance, dominance of controlling shareholders, and the focus of large companies on long-term growth are more decisive in determining the direction of dividend policy, so that the effectiveness of external and internal supervision is contextual and not linear to the scale of the company. The implication is that regulators and companies need to review the effectiveness of the role of independent commissioners and encourage the involvement of foreign investors as a strategic oversight mechanism, regardless of the scale of the company.